HUMANISME SPIRITUAL: Konseptualisasi dan Performansi Melalui Pendidikan Islam - Prabowo Adi Widayat (Tarbawiyah Jurnal Ilmiah Pendidikan, 2018)
Humanism rooted and growing in every human life is a conceptual mission humanity in space and time. Humanism always brings the concept of alignment, honor, and dignity of human beings in various dimensions to understand his position and implemented in the social life. Spirituality is an urge from within human sourced from a deep spiritual side. He is abstract and made life path combined with elements of religious and socio-cultural values rooted stronger. Spiritual humanism is a humanitarian concept which represents a side of distinctiveness, uniqueness, advantages and disadvantages that exist in human beings by referencing only at teoantropocentric which makes aspects divinity of Allah SWT with all its affordability and man with the potential to make it more meaningful and meaningless in the course of an increasingly complex life obstacles. Islamic education became an important locomotive in the embodiment of spiritual humanism within the framework of theoretical or scientific knowledge of Islam and is pragmatic in the vertical and horizontal form of worship.